1981
DOI: 10.2307/2287597
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Based Tests of Uniformity

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Statistical Association is collaborating with JSTOR to digitize, preserve and extend access to Journal of the American Statistical Association.The power properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(53 citation statements)
references
References 6 publications
0
53
0
Order By: Relevance
“…Vasicek (1976), Arizono and Ohta (1989), Dudewicz and Van Der Meulen (1981) as well as Ebrahami et al (1992) have demonstrated that the test statistic (2.4) with optimal values of m provides very powerful tests for normality, uniformity and exponentiality. Note that the authors obtained (2.4)-type test-statistics via estimation of the sample entropy (e.g., Vasicek 1976).…”
Section: Entropy-based Empirical Likelihood Approximation To Parametrmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasicek (1976), Arizono and Ohta (1989), Dudewicz and Van Der Meulen (1981) as well as Ebrahami et al (1992) have demonstrated that the test statistic (2.4) with optimal values of m provides very powerful tests for normality, uniformity and exponentiality. Note that the authors obtained (2.4)-type test-statistics via estimation of the sample entropy (e.g., Vasicek 1976).…”
Section: Entropy-based Empirical Likelihood Approximation To Parametrmentioning
confidence: 99%
“…Note that, a very substantial body of literature has now grown around the asymptotic distribution problems involving the Vasicek's entropy estimator and the analogous statistics (e.g., Dudewicz and Van Der Meulen 1981;van Es 1992). However, it is generally recognized that even the asymptotic distribution of the statistic T mk by (2.4), which can depend on estimates of nuisance parameters of f 0 , is analytically difficult.…”
Section: Critical Values Of the Proposed Test Our Test Statistic Is Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches were applied to estimate entropy and based on the new introduced estimators (e.g. modified Vasicek's estimator [37,38], Noughabi's entropy estimator [39]) new goodness-of-fit tests were developed and performances in testing the normal [40][41][42], lognormal [43], uniform [44][45][46], exponential [47], beta [47,48], Poisson [49], Weibull [43], Gamma [43], Pareto [50,51], Student and exponential distribution [52] were studied.…”
Section: Shannon's Entropy Statisticmentioning
confidence: 99%
“…Prescott (1976) using sensitivity contours showed that entropy test is considerably less sensitive to outliers than the one given by Shapiro-Wilk. Dudewicz and van der Muelen (1981) established a test for uniformity and they showed that this entropy test possesses good power properties for many alternatives. Menendez et al (1997) presented an estimator and a test statistic for goodness of fit based on Shannon's entropy and maximum entropy principle with order statistics.…”
Section: Introductionmentioning
confidence: 99%